Hubungan Filsafat Ilmu Terhadap Perkembangan Pendidikan - Rahmat (Jurnal Edukasi, 2022)
The philosophy of science is understood as a branch of philosophy that emerged in the late 19th century or entered the 20th. The development of science and the development of education reached their peak in the nineteenth century at the time of August Comte and his successors, who tended to measure the truth of science on the scale of the philosophical flow based on something real, making science more and more independent of the basic assumptions of its philosophies. The philosophy of science also tries to introduce science in its entirety. In essence, the philosophy of science can stand in the middle of the branch of science with various rules and guidelines for the application of educational principles. As for the relationship of the philosophy of science to the development of education, it is a human effort to understand the concept and method of a discipline of science. Changes and developments have brought philosophies into a configuration by showing how science evolves with each discipline.